2021
DOI: 10.1002/adfm.202101638
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire Assisted Mechanotyping of Cellular Metastatic Potential

Abstract: Nanotechnology has provided tools for next generation biomedical devices which rely on nanostructure interfaces with living cells. In vitro biomimetic structures have enabled observation of cell response to various mechanical and chemical cues, and there is a growing interest in isolating and harnessing the specific cues that 3D microenvironments can provide without the requirement for such culture and the experimental drawbacks associated with it. Here, a randomly oriented gold coated Si nanowire substrate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…In this research, we have demonstrated the realization of a platform for EV capture and the simultaneous differentiation and proliferation of DCs. Conventional ZnO nanowires effectively captured the EVs, but they were proved to be cytotoxic in this study, which is consistent with the literature; however, it is possible to remove the toxicity by forming a protective film using another metal oxide, which will satisfy EV capture and cell culture requirements simultaneously. DCs are generally considered the starting point of acquired immunity, and in conventional DC vaccine therapy, tumor tissue is administered to DCs to take up and present the tumor-associated antigen.…”
Section: Discussionsupporting
confidence: 90%
“…In this research, we have demonstrated the realization of a platform for EV capture and the simultaneous differentiation and proliferation of DCs. Conventional ZnO nanowires effectively captured the EVs, but they were proved to be cytotoxic in this study, which is consistent with the literature; however, it is possible to remove the toxicity by forming a protective film using another metal oxide, which will satisfy EV capture and cell culture requirements simultaneously. DCs are generally considered the starting point of acquired immunity, and in conventional DC vaccine therapy, tumor tissue is administered to DCs to take up and present the tumor-associated antigen.…”
Section: Discussionsupporting
confidence: 90%
“…In this regard, randomly organized nanostructures with non‐uniform size distribution are gaining significant attention as suitable interface for cellular cultures. [ 29 , 30 , 31 ] Specifically, disordered silicon nanowires (SiNWs) offer unprecedented versatility in terms of mammalian cell interfacing [ 29 , 31 , 32 ] due to their architecture mimicking the extracellular matrix, and as probes of cellular function and biomolecules through electrical and optical signal transduction. [ 31 , 33 , 34 , 35 , 36 , 37 ] Moreover, these systems can be easily obtained by using low‐cost, high‐yield and facile bottom‐up fabrication methods at low temperature (<350 °C) [ 35 , 38 ] thus permitting their direct growth on specific flexible substrates like as polyimide.…”
Section: Introductionmentioning
confidence: 99%
“…For example, metal nanoparticles (NPs) have been demonstrated as effective photothermal agents for in vivo imaging and destruction of cancer cells [3][4][5] as well as targeted drug nanocarriers [6,7]. In vitro, other nanomaterials such as silicon nanowires (SiNWs) have shown tremendous promise in recording extracellular and intracellular bioelectrical signals [8][9][10][11], destroying tumor cells [12], detecting very low concentrations of different biomolecules [13][14][15][16], and offering mechanotyping possibilities [17,18].…”
Section: Introductionmentioning
confidence: 99%